2022
DOI: 10.1155/2022/1032976
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Personalised Recommendation of PE Network Course Environment Resources Using Data Mining Analysis

Abstract: PE education reform is positively influenced by the creation and use of resources for PE courses as a supplement to and development of traditional teaching strategies. In order to mine the vast amount of data in the network PE curriculum resource system and find useful patterns, this paper uses highly automated DM technology. Additionally, you can forecast users’ upcoming actions and suggest particular course resources to them. This recommendation system makes course resources that users might be interested in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Online education has flourished, in general. It breaks the traditional education model and realizes leapfrog teaching on the internet in different periods (Yu et al, 2018;Min, 2022;Wang et al, 2019a;Zhang et al, 2017). There is much useful information on many social networking sites for consumers to compare products.…”
Section: Introductionmentioning
confidence: 99%
“…Online education has flourished, in general. It breaks the traditional education model and realizes leapfrog teaching on the internet in different periods (Yu et al, 2018;Min, 2022;Wang et al, 2019a;Zhang et al, 2017). There is much useful information on many social networking sites for consumers to compare products.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Zhang [23] proposed a recommended online sports course resource method based on collaborative filtering technology. Min [24] used highly automated data mining (DM) technology to predict users' upcoming actions and recommend specific course resources. Diao et al [25] proposed a personalized learning resource recommendation framework based on course ontology and learners' cognitive ability.…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%